1978
DOI: 10.1111/j.1399-3011.1978.tb02841.x
|View full text |Cite
|
Sign up to set email alerts
|

Chains of Alternating Sulfur and Π‐bonded Atoms in Eight Small Proteins

Abstract: This paper demonstrates the existence of regions in eight small globular proteins in which the side chains of sulfur‐containing amino acids (cysteine and methionine) alternate in space with side chains of aromatic amino acids (histidine, phenylalanine, tryptophan and tyrosine). The proteins are: rubredoxin, high potential iron protein, cytochrome c, flavodoxin, deoxyhemoglobin, trypsin inhibitor, ribonuclease‐S, and lysozyme. The sulfur‐φ‐bonded ‘chains’ involve a minimum of five and a maximum of 10 amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(79 citation statements)
references
References 14 publications
4
75
0
Order By: Relevance
“…The higher-than-expected frequency of sulfur-and aromatic-containing residues in close proximity was first noted in a brief bioinformatics study of eight protein structures (1,2). More extensive bioinformatics results extended these findings to include additional protein complexes as well as small molecules (3)(4)(5).…”
supporting
confidence: 50%
“…The higher-than-expected frequency of sulfur-and aromatic-containing residues in close proximity was first noted in a brief bioinformatics study of eight protein structures (1,2). More extensive bioinformatics results extended these findings to include additional protein complexes as well as small molecules (3)(4)(5).…”
supporting
confidence: 50%
“…The S· · · π interactions in proteins were first pointed out by Morgan and co-workers [60], who analyzed the close atomic contact between S and a π-ring system in eight protein structures and found that the S atoms have a propensity to come over the π-plane. On the other hand, Reid et al [61] suggested by using a larger set of protein structures that the close S· · · π contact in proteins can also be explained by C-H· · · S interactions because the S atoms access to the π-plane from the side rather than the top.…”
Section: Discovery Of S· · · X Chalcogen Bonds In Proteinsmentioning
confidence: 99%
“…Pt (1) Sulfur-p interactions have been relatively little studied compared to other types of p interactions, but the observation that these might play a significant role in the structures of sulfur-containing proteins [25] has led to theoretical studies of S-p interacting systems such as the H 2 S-benzene dimer (though in this system the interaction is between the d+ hydrogens and the dÀ benzene ring) [26]. Such an interaction in 3 is promoted by the positive charge at the centre of the fluoroaryl ring [27], which interacts (as an electron acceptor) with the electron-rich sulfide donor of the {Pt 2 S 2 } core.…”
Section: X-ray Structure Determination On [Pt 2 (L-s)(l-sch 2 C 6 F 5mentioning
confidence: 98%